2020
DOI: 10.1186/s12974-019-1692-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation trajectories precede cognitive impairment after experimental meningitis—evidence from an in vivo PET study

Abstract: Background: Bacterial meningitis is a devastating central nervous system (CNS) infection with acute and long-term neurological consequences, including cognitive impairment. The aim of this study was to understand the association between activated microglia-induced neuroinflammation and post-meningitis cognitive impairment. Method: Meningitis was induced in male Wistar rats by injecting Streptococcus pneumoniae into the brain through the cisterna magna, and rats were then treated with ceftriaxone. Twenty-four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Microglial cells are highly specialized tissue macrophages of the CNS [34], and the dysregulation of this cell type triggers neuropsychiatric, neurodegenerative, and neuroinflammatory diseases [35]. Using positron emission tomography (PET) imaging with [ 11 C]PBR28, a radiotracer ligand that binds to 18-KDa translocator protein (TSPO), we identified in vivo microglia activation 10 days after meningitis induction [36] . Similarly, in this research strategy, microglia cells (IBA-1 and CD11B) were activated at 10 days after meningitis induction concomitant with an increase in RAGE and Aβ 1-42 expression in the PFC and hippocampus of meningitis survivor rats.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells are highly specialized tissue macrophages of the CNS [34], and the dysregulation of this cell type triggers neuropsychiatric, neurodegenerative, and neuroinflammatory diseases [35]. Using positron emission tomography (PET) imaging with [ 11 C]PBR28, a radiotracer ligand that binds to 18-KDa translocator protein (TSPO), we identified in vivo microglia activation 10 days after meningitis induction [36] . Similarly, in this research strategy, microglia cells (IBA-1 and CD11B) were activated at 10 days after meningitis induction concomitant with an increase in RAGE and Aβ 1-42 expression in the PFC and hippocampus of meningitis survivor rats.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer’s instructions, the protein estimation was performed using a Micro BCA ® protein assay kit for the sample submitted for immunoblotting, cytokine assay, and ELISA (Thermo Fischer Scientific, MA, USA) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BBB transport and glymphatic clearances are interdependent mechanisms, and the dysfunction of these mechanisms can difficult the solute clearance [36]. The BBB permeability or disruption facilitates the migration of peripheral immune cells and inflammatory mediators into the CSF, increasing the production of cytokines, chemokines, reactive oxygen and nitrogen species, and neurotoxic molecules that contribute to glial cell activation and consequent neuroinflammation [6, 7, 8, 9]. Pre-clinical studies of bacterial meningitis have demonstrated that the BBB breakdown is associated with cognitive impairment [37, 38], and when the proteolytic enzymes like matrix metalloproteinases (MMPs) were blocked cognitive dysfunction could be prevented [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation triggered by the host immune response leads to the recruitment of peripheral immune cells into the brain and the cerebrospinal fluid (CSF) in a tentative to eliminate the invasive pathogens [6]. The inflammatory mediators which are released in the brain during the infection include cytokines, chemokines, reactive oxygen and nitrogen species, and neurotoxic molecules that contribute to the activation of the microglial cells, initiating neuroinflammation [7, 8, 9]. All these waste products, including host-derived debris, and the invading pathogen itself along with any secreted toxins, are released in the CSF and in the brain parenchyma and must be efficiently cleared from the brain to regain CNS homeostasis.…”
Section: Introductionmentioning
confidence: 99%